The effect of Dodonaea viscosa var. Angustifolia (L.F.) on the ultrastructure of Candida albicans cell wall and biofilm formation - Naicker, Serisha Devi (My University, 2012)
Oral candidiasis is an infection prevalent in immunocompromised individuals. The main causative agent is Candida albicans. Many antifungal agents are available and are effectively used. However, due to the development of drug resistance, toxicity and poor solubility resulting in poor absorption; medicinal plants have been investigated. Dodonaea viscosa var. angustifolia, an indigenous South African plant has shown to have an antifungal effect including inhibition of adherence of C. albicans to oral epithelial cells; which is the crucial first step of infection. This study investigated the effect of the crude extract on the ultrastructure of C. albicans cell wall, which might be responsible for the reduced adherence to oral epithelial cells. The effect of the plant extract on C. albicans germ tube and biofilm formation was also studied since biofilm structure allows for high resistance to antifungal agents and host defense mechanisms. Crude plant extracts were prepared using dried leaves and acetone. Three C. albicans strains were used throughout the study. Minimal fungicidal concentrations of plant extract were determined using a microdilution technique. Three subinhibitory concentrations 3.125, 1.562 and 0.781 mg/ml were selected for further studies. The effect of these subinhibitory concentrations of plant extract on the C. albicans cell wall structure, cell membrane, germ tube formation, biofilm formation and cell wall proteins were studied using transmission electron microscopy, light microscopy, scanning electron microscopy and SDS-PAGE respectively. v The subinhibitory concentrations of crude plant extract rendered C. albicans cell wall thinner and at some places caused cell wall breakage and disruption. This effect increased with a decrease in plant extract concentration. The cell membrane was also damaged by the plant extract showing increased undulation. This effect was not concentration dependent. The subinhibitory concentrations decreased C. albicans germ tube formation and the effect increased with an increase in concentration. Biofilm formation was reduced by the plant extract and in addition, hyphal formation by cells within the biofilm was also reduced. However, SDS-PAGE showed that on a molecular level, the plant extract did not remove any specific adhesin proteins from the cell wall. The crude plant extract of D. viscosa var. angustifolia at high concentrations, kills C. albicans and at low concentrations, renders the surviving cells avirulent. Therefore it has the potential to be developed into an effective therapeutic agent to treat and prevent oral candidiasis. However, further research is required to identify the mode of action of the extract, the specific chemicals responsible for the effect, and the cytotoxicity.
Dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Master of Science in Medicine. Johannesburg, 2012
Keywords: Candida albicans; Plants, Medicinal